Haemophagocytic lymphohistiocytosis associated with bartonella peliosis hepatis following kidney transplantation in a patient with HIV. Issue 10 (October 2022) - Steed, Danielle; Collins, Jeffrey; Farris, Alton B; Guarner, Jeannette; Yarar, Dilek; Friedman-Moraco, Rachel; Doane, Tristan; Pouch, Stephanie; Marshall Lyon, G; Woodworth, Michael H
Summary: Bacillary peliosis hepatis is a well recognised manifestation of disseminated Bartonella henselae infection that can occur in immunocompromised individuals. Haemophagocytic lymphohistiocytosis is an immune-mediated condition with features that can overlap with a severe primary infection such as disseminated Bartonella spp infection. We report a case of bacillary peliosis hepatis and secondary haemophagocytic lymphohistiocytosis due to disseminated Bartonella spp infection in a kidney-transplant recipient with well controlled HIV. The patient reported 2 weeks of fever and abdominal pain and was found to have hepatomegaly. He recalled exposure to a sick dog but reported no cat exposures. Laboratory evaluation was notable for pancytopenia and cholestatic injury. The patient met more than five of eight clinical criteria for haemophagocytic lymphohistiocytosis. Pathology review of a bone marrow core biopsy identified haemophagocytosis. A transjugular liver biopsy was done, and histopathology review identified peliosis hepatis. Warthin–Starry staining of the bone marrow showed pleiomorphic coccobacillary organisms. The B henselae IgG titre was 1:512, and Bartonella -specific DNA targets were detected by peripheral blood PCR. Treatment with doxycycline, increased prednisone, and pausing the mycophenolate component of his transplant immunosuppression regimen resulted in an excellent clinical response. Secondary haemophagocytic lymphohistiocytosis can be difficult to distinguish from severe systemic infection. A high index of suspicion can support the diagnosis of systemic Bartonella spp infection in those who present with haemophagocytic lymphohistiocytosis, especially in patients with hepatomegaly, immunosuppression, and germane animal exposures.